
Hãy nhập câu hỏi của bạn vào đây, nếu là tài khoản VIP, bạn sẽ được ưu tiên trả lời.




\(=\frac{11.3^{22}.3^7-9^{15}}{\left(2.3^{14}\right)^2}\)
\(=\frac{11.3^{29}-\left(3^2\right)^{15}}{2^2.3^{14.2}}\)
\(=\frac{11.3^{29}-3.3^{29}}{2^2.3^{28}}\)
\(=\frac{\left(11-3\right).3^{29}}{2^2.3^{28}}\)
\(=\frac{8.3^{29}}{4.3^{28}}\)
\(=6\)

(\(\frac{15}{22}\)-\(\frac{7}{13}\)) x \(\frac{13}{7}\)- \(\frac{15}{22}\) x(\(\frac{6}{7}\)- \(\frac{22}{15}\))
=(\(\frac{15}{22}\)x \(\frac{13}{7}\)- 1) - \(\frac{15}{22}\)x\(\frac{6}{7}\)-1
=\(\frac{15}{22}\)x \(\frac{13}{7}\)-\(\frac{15}{22}\)x\(\frac{6}{7}\)(vì -1+1=0)
=\(\frac{15}{22}\)x(\(\frac{13}{7}\)-\(\frac{6}{7}\))
=\(\frac{15}{22}\)
làm hơi tắt nha
\(\left(\frac{15}{22}-\frac{7}{13}\right).\frac{13}{7}-\frac{15}{22}.\left(\frac{6}{7}-\frac{22}{15}\right)\)
\(=\frac{15}{22}.\frac{13}{7}-\frac{7}{13}.\frac{13}{7}-\frac{15}{22}.\frac{6}{7}+\frac{15}{22}.\frac{22}{15}\)
\(=\frac{15}{22}.\left(\frac{13}{7}-\frac{6}{7}\right)-1+1\)
\(=\frac{15}{22}.1-1+1\)
\(=\frac{15}{22}-\left(1-1\right)\)
\(=\frac{15}{22}-0\)
\(=\frac{15}{22}\)

Tính: \(=\frac{11.3^{22+7}-\left(3^2\right)^{15}}{2^2.\left(3^{14}\right)^2}=\frac{11.3^{29}-3^{30}}{4.3^{28}}=\frac{3^{28}\left(11.3-3^2\right)}{4.3^{28}}=\frac{24}{4}=6\)
Tìm x:
<=> (2x-15)7- (2x-15)5=0
<=> (2x-15)5 .[(2x-15)2-1]=0
<=> (2x-15)5 = 0 hoặc (2x-15)2-1 = 0
+) (2x-15)5=0 <=> 2x - 15 = 0 <=> x = 15/2
+) (2x-15)2 - 1 = 0 <=> (2x-15)2 = 1 <=> 2x - 15 = 1 <=> 2x = 16 <=> x = 8 hoặc 2x - 15 = -1 <=> 2x = 14 <=> x = 7
Vậy x = {15/2 ; 8 ; 7}
tìm chứ số tận cùng
5833= 58.5832 = 58. (582)16 = 58. (....4)16 = 58. (....42)8 = 58. (....6)8 = 58 x ....6 =....8

\(\frac{11.3^{29}-\left(3^2\right)^{15}}{2^2.\left(3^{14}\right)^2}=\frac{11.3^{29}-3^{30}}{2^2.3^{28}}=\frac{3^{29}.\left(11-3\right)}{2^2.3^{28}}=\frac{3^{28}.3.2^3}{2^2.3^{28}}=6\)
\(=\frac{11.3^{29}-\left(3^2\right)^{15}}{2^2.3^{28}}=\frac{11.3^{29}-3^{30}}{4.3^{28}}=\frac{3^{29}.\left(11-3\right)}{4.3^{28}}=\frac{3.8}{4}=6\)
a,(x-15):5+22=24
b,|x+7|=15-(-4)
c,\(\left(x-\frac{1}{2}\right):\frac{1}{3}+\frac{5}{7}=9\frac{5}{7}\)


=3/22-(7/15+3/22)+7/15-1/2
=3/22-7/15-3/22+7/15-1/2
=(3/22-3/22)+(7/15-7/15)-1/2
=0+0-1/2
=-1/2
`3/22 - (7/15 - (-3)/22) + 7/15 - 1/2`
`= 3/22 - (7/15 + 3/22) + 7/15 -1/2`
`= 3/22 - 7/15 - 3/22 + 7/15 -1/2`
`= (3/22 -3/22) +(-7/15 + 7/115)-1/2`
`= 0 + 0-1/2`
`=-1/2`